AKSELERASI PENYELENGGARAAN ELEKTRONIK PERADILAN DI SATUAN KERJA PENGADILAN BARU: Refleksi Penerapan e-Court dan e-Litigasi di Pengadilan Agama Kuala Pembuang - Apriandi, Eko Apriandi (Judex Laguens, 2023)
The development of information technology has an impact on the world of law and justice, one of which is the implementation of electronic courts in the Supreme Court and the judicial bodies under it. The implementation of electronic justice is an obstacle for newly formed courts such as the Kuala Pembuang Religious Court. Therefore, this research aims to describe the implementation of electronic justice in the new court work unit of the Kuala Pembuang Religious Court and describe efforts to accelerate the implementation of electronic justice in the Kuala Pembuang Religious Court. This research is a qualitative legal research with a normative approach and uses a descriptive analysis method. The results showed: first, the Kuala Pembuang Religious Court as a new court work unit has implemented electronic justice through e-Court and e-Litigation well since 2019. Second, acceleration efforts have been maximized to improve the implementation of electronic justice at the Kuala Pembuang Religious Court with the result of a significant increase.